Formulating strategies to strengthen resilient MSMEs in the F&B sector of Central Java: An integrated SWOT, IFE, EFE, IE, and QSPM approach - Dini, Ines; Janet, Marcia (Privietlab, 2024)
This study aims to formulate strategies to strengthen “Resilient MSMEs” in the food and beverage (F&B) sector in Central Java using an integrative approach that combines SWOT, IFE, EFE, IE, and QSPM analyses. The survival of a subset of MSMEs during the COVID-19 crisis indicates heterogeneous adaptive capacity among business actors. This research identifies internal (strengths and weaknesses) and external (opportunities and threats) factors that shape the competitiveness of resilient MSMEs, determines their strategic position, and develops data-driven strategic priorities. A mixed-methods design was employed, with data collected through in-depth interviews and questionnaires administered to 13 resilient F&B MSMEs. The results show an IFE score of 3.26 and an EFE score of 3.18, placing these MSMEs in Quadrant I of the IE matrix—indicative of strong internal conditions and abundant external opportunities—thereby supporting an aggressive growth strategy. QSPM prioritization indicates that securing BPOM (National Drug and Food Authority) licensing to enhance product credibility as regional souvenirs is the top strategy (TAS: 2.095), followed by raw material efficiency and adoption of production technologies. Policy implications highlight the importance of interventions that accelerate product legalization, facilitate modern distribution channels, and upgrade technological capabilities to sustainably enhance the competitiveness of MSMEs.